ASSOCIATION OF VITAMIN B12 DEFICIENCY WITH INTAKE OF ORAL METFORMIN IN DIABETIC PATIENTS - Hasan, Najam Ul; Makki, Mujeeb Ullah; Abid, Izza; Butt, Mujeeb Ur Rehman Abid (Journal of Ayub Medical College Abbottabad, 2018)
Background: It is estimated that 450 million people worldwide have diabetes mellitus Objective of the study was to determine effect of Metformin on vitamin B12 level among patients with type 2 diabetes mellitus. It is a cross sectional study conducted at Medicine department, Shalamar Hospital Lahore. Methods: Seventy-two patients of diabetes mellitus were included in the study. All patients who could have any other disease process that can lead to Vitamin B12 deficiency were excluded from the study. They were segregated into two groups, first one was getting metformin for the last 2 years and the second group was not taking metformin. Vitamin B12 levels were checked in all the patients and value of 150pmol/L was taken as normal. Results: Out of 72 patients who participated in our study, 40 patients (55.5%) were taking metformin for more than two years while 32 patients (44.5%) were not taking metformin for the last two years. Mean age of patients taking metformin and not taking metformin was 59±9.12 years and 60±5.47 years respectively. Mean vitamin B12 level was 360±185.2 pg/ml in patients taking metformin while among non-metformin group mean vitamin B12 level was 619±176 pg/ml (p value=0.0001). Furthermore, HbA1c and MCV were significantly different among metformin group and non-metformin group, i.e., p=0.034 and 0.039 respectively. Among metformin group, age and MCV were also significantly different in those having vitamin B12 deficiency and those having normal Vitamin B12 levels, i.e., p=0.042 and 0.001 respectively. Conclusion: It was concluded from our study that long term (>2 years) use of metformin is significantly associated with vitamin B12 deficiency. Keywords: Metformin; Vitmain B12, Diabetes, HbA1c